Recent advancements in hematopoietic stem cell transplantation in Taiwan - Chi-Cheng Li; Xavier Cheng-Hong Tsai; Wei-Han Huang; Tso-Fu Wang (Tzu Chi Medical Journal)
Hematopoietic stem cell transplantation (HSCT) can cure malignant and nonmalignant hematological disorders. From 1983 to 2022, Taiwan performed more than 10,000 HSCT transplants. The Taiwan Blood and Marrow Transplantation Registry collects clinical information to gather everyone's experience and promote the advances of HSCT in Taiwan to gather everyone's experience and promote advances of HSCT in Taiwan. Compared with matched sibling donors, transplants from matched unrelated donors exhibited a trend of superior survival. In Taiwan, transplant donors showed remarkable growth from unrelated (24.8%) and haploidentical (10.5%) donors. The number of older patients (17.4%; aged ≥61 years) who underwent transplantation has increased markedly. This review summarizes several significant developments in HSCT treatment in Taiwan. First, the use of Anti-thymocyte globulin (ATG) and intravenous busulfan regimens were important risk factors for predicting hepatic sinusoidal obstruction syndrome. Second, a new, machine learning-based risk prediction scoring system for posttransplantation lymphoproliferative disorder has identified five risk factors: aplastic anemia, partially mismatched related donors, fludarabine use, ATG use, and acute skin graft-versus-host disease. Third, although the incidence of idiopathic pneumonia syndrome was low (1.1%), its mortality rate was high (58.1%). Fourth, difficult-to-treat mantle cell and T-cell lymphomas treated with autologous HSCT during earlier remission had higher survival rates. Fifth, treatment of incurable multiple myeloma with autologous HSCT showed a median progression-free survival and overall survival of 46.5 and 70.4 months, respectively. Sixth, different haploidentical transplantation strategies were compared. Seventh, caution should be taken in administering allogeneic HSCT treatment in older patients with myeloid leukemia with a Charlson Comorbidity Index ≥3 because of a higher risk of nonrelapse mortality.